YouTubeTM as a Tool to Teach Dentists about Molar Incisor Hypomineralization (MIH): Analysis of Quality Content - Danielle Fernandes da Silva; Ana Carolina Lobosco; Fernanda Mafei Felix da Silva; Marcela Baraúna Magno (Association of Support to Oral Health Research (APESB), 2023)
Objective: To evaluate the quality of information about Molar incisor Hypomineralization (MIH) on YouTubeTM. Material and Methods: Only videos in Portuguese aimed at dentists were included. The selected videos were analyzed by two calibrated evaluators, who extracted the information (classification, etiology, diagnosis, and treatment of MIH) and the quality was evaluated through a 20-point-checklist, according to the International Association of Pediatric Dentistry and European Academy of Pediatric Dentistry. Descriptive analysis and statistical tests were applied to assess the association (ANOVA and Kruskal-Wallis) or correlation (Spearman) between the final scores of the videos and their demographics. Results: Nineteen videos with 13.8±4.76 mean points were considered eligible. Most of the videos did not report the possible involvement of other groups of teeth (n=12), presence of atypical restorations (n=8) and hypersensitivity (n=7); and the different treatments for MIH were very variable.  Twelve videos discussed differential diagnosis and 78.95% possible etiological factors; however, all of them presented clinical images. Data related to the video source and viewer interaction were not related to its quality (p>0.05). The number of likes (r=0.26), views (r=0.34) and video time (=0.58) show a weak and moderate correlation, respectively, with video score. Conclusion: Videos on YouTubeTMabout MIH presented moderate or high quality, with heterogeneous information, and can act as a complementary aid source of information.